2006
DOI: 10.1088/0964-1726/15/4/014
|View full text |Cite
|
Sign up to set email alerts
|

A two-dimensional finite element analysis of a shape memory alloy laminated composite plate

Abstract: The deflection and time response of shape memory alloy laminated composite plate are studied using first order shear deformation theory. The composite plate consists of a thin layer of shape memory alloy bonded to an elastomer layer. The governing equations of the plate are developed using the energy balance equations and a two-dimensional model of the shape memory alloy layer. The finite element is modeled with the first order shear deformation theory and equivalent single layer assumptions. The model is vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…The variations in martensite fraction in the activated SMA layer using the linear and Brinson's models are shown in Figure 2. in comparison with the results obtained by Balapgol [3], and Ghomshei [2]. A good agreement is found between the proposed model and the mentioned references results.…”
Section: Case (I): Free Thermal Response Of Sma Laminated Platesupporting
confidence: 87%
See 3 more Smart Citations
“…The variations in martensite fraction in the activated SMA layer using the linear and Brinson's models are shown in Figure 2. in comparison with the results obtained by Balapgol [3], and Ghomshei [2]. A good agreement is found between the proposed model and the mentioned references results.…”
Section: Case (I): Free Thermal Response Of Sma Laminated Platesupporting
confidence: 87%
“…During martensitic transformation of SMA the modulus of elasticity of the metal is uniformly blended with the martensite and austenite phases [3]. The SMA layer and the host layers are perfectly bonded.…”
Section: Stress-strain Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, due to the diffusion of Ti from TiNi alloys to the interface of composite, another diffused layer about 4 lm was formed in the TiNi fiber next to the interfacial layer. It was confirmed that the atomic ratio of Ti and Ni in TiNi alloy had a great influence on the temperature of martensitic transformation [25]. The decrease of atomic ratio of Ti and Ni in the diffused layer was induced by the diffusion of Ti atom.…”
Section: Applicationsmentioning
confidence: 82%